"اثر الطاقات المتجددة في تنويع الصادرات السلعية دراسة قياسية لدولة الامارات العربية للفترة ما بين 2007 الى 2021" - ضياء الحق, بالصالحة; عبد الحميد, بوغزالة امحمد; العيد, بوغزالة امحمد (جامعة الوادي - University of Eloued, 2023)
"الملخص : تهدد هد الدراسدة قيداس ر در الطاقدات المتجدددة علدى تنافسدية الصدادرات السدلعية وقدد الاعتمداد علدى مؤشدر التنويدع للصدادرات كمتغدير تدابع و مدن خدلال بياندات سدنوية خدلال الفدترة ال منيدة ( 2007 - 2021 ( لدولدة الامدارات العربيدة المتحددة ولتحقيدل ذلدا اسدت دم الدراسدة الا ددار المتعدد باست دام طريقة المربعدات الصدغرا العاديدة وبالاسدتعانة ببرندامج 12 EVIEWS. خلصد النتدائج الى رن الطاقدات المتجدددة مدن خدلال اسدت لاي الطاقدة المتجدددة يدؤ ر ا ابدا علدى تنافسدية الصدادرات في الامدارات رمدا بداقي المتغديرات المسدتقلة الأخدرا ف نداي ر در سدلبي للت د م علدى تنافسدية الصادرات في حين عدم وجود ر ر لنمو نصيب الفرد من الناتج المحلدي علدى تنافسدية الصدادرات وامدا الاستثمار الأجنبي المباشر فله ر ر ا ابي على تنافسية الصادرات لدولة الامارات" This study attempts to measure the impact of renewable energies on the competitiveness of commodity exports. The export diversification index was relied upon as a dependent variable and through annual data during the time period (2007 2021) for the United Arab Emirates. To achieve this, the study used multiple regression using the ordinary least squares method. Using the 12 EVIEWS program. The results concluded that renewable energies through the consumption of renewable energy positively affect the competitiveness of exports in the Emirates, and as for the rest of the other independent variables, there is a negative effect of inflation on the competitiveness of exports, while there is no effect of the growth of the per capita share of domestic product on the competitiveness of exports, and as for foreign investment Directly, it has a positive impact on the competitiveness of exports to the UAE
Keywords: الطاقات المتجددة ، الصادرات السلعية ،دولة الامارات العربية